Philosophy and the Philosophers in Tom Stoppard’s Later Plays (Филологический класс, 2023)
Tom Stoppard’s ‘science dramas’ have been mostly associated with Hapgood (1988), where Spy games were interwoven with Heisenberg’s uncertainty principle, and Arcadia (1993), one of the most famous play, united mathematics, landscape design, literary history, and Chaos theory. But there are also philosophy plays, such as Jumpers (1972) and Professional Foul (1977), among Stoppard’s works. The playwright appeals to Cambridge Analytic philosophy of Bertrand Russell, George E. Moore, and Ludwig Wittgenstein in the 1970s plays, combining proper philosophical, logical and ethical questions, and then keeps regarding the history of philosophy and the philosophy of history in his later plays. The article considers Stoppard’s later plays The Hard Problem (2015) and Leopoldstadt (2020) in concern with the history of science in theatre. The Hard Problem deals with the problem of consciousness which is fundamental for the heroes of the play; the range of philosophical allusions is significantly updated here. The characters of the play serve at “the Krohl Institute for Brain Science”, they debate the newest achievements of psychological science and of the ‘philosophy of consciousness’. Contemporary scholars Richard Dawkins, Thomas Nagel, John Searle, D. S. Wilson are named by the playwright himself as the authors of the books, Stoppard is ‘in debt to’, ‘as for the science in The Hard Problem’. The ideas of philosophers are actively ‘quoted’ by the characters, helping them to build different points of view on the problems of ‘mindbody’, ‘brain-computer’ or of ‘altruism vs egoism as the basement of human behavior’. As a result, Hilary, the protagonist, “is not proud to be a materialist”. Leopoldstadt is a play about the Holocaust and it is considered as the most personal Stoppard’s play up to the moment. The play presents the story of an extended Austrian-Jewish family whose many members became the victims of the Holocaust. There is a historical collision in the play, but T. Stoppard includes the figures or ideas of Sigmund Freud and Ludwig Wittgenstein to create the cultural context of Vienna before the WWII. Freud is regarded as a symbol of Austrian culture and as to some extent a prophet of ‘the nightmares’ in the history of the 20th century. Wittgenstein and his philosophy of language have been of permanent interest for the dramatist. Nevertheless, in Leopoldstadt there is an allusion to the history of the Wittgenstein family and to Alexander Waugh’s book The House of Wittgenstein. A Family at War. It is typical for the playwright’s style that philosophical or political debates in his drama correlate with Stoppard’s theatrical and literary experiments. The article considers different possibilities of presenting philosophical ideas and moral concepts in the plays by Stoppard.